Traces of An Early Learned Second Language in Discontinued Bilingualism. (7th September 2016) - Sadat, Jasmin; Pureza, Rita; Alario, F.‐Xavier
Abstract : Can an early learned second language influence speech production after living many years in an exclusively monolingual environment? To address this issue, we investigated the consequences of discontinued early bilingualism in heritage speakers who moved abroad and switched language dominance from the second to the primary learned language. We used two fluency tasks to compare European Portuguese monolinguals with early European Portuguese‐French bilinguals who no longer use French. The occurrence of cognate words in retrieval performance was used as an index for the influence of the early learned second language (French). Results showed that bilinguals used more cognates than noncognates relative to monolinguals. Also, monolinguals and bilinguals produced the same number of responses in the fluency tasks, and the produced words were of similar frequency. Our findings highlight that early learning of a second language, even when discontinued, plays a lasting role for word selection.